2002
DOI: 10.1590/s0100-879x2002000900006
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in vascular expression of endothelin and ET A/ET B receptors, but not in calcium handling mechanisms, in deoxycorticosterone acetate-salt hypertension

Abstract: We determined if the increased vascular responsiveness to endothelin-1 (ET-1) observed in male, but not in female, DOCA-salt rats is associated with differential vascular mRNA expression of ET-1 and/ or ET A /ET B receptors or with functional differences in Ca 2+ handling mechanisms by vascular myocytes. Uninephrectomized male and female Wistar rats received DOCA and drinking water containing NaCl/KCl. Control rats received vehicle and tap water. Blood pressure and contractile responses of endothelium-denuded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
(27 reference statements)
1
22
0
2
Order By: Relevance
“…Changes in ET Bmediated vascular responses were associated with increased ET-1 and ET B receptor gene expression in male, but not in female, animals (49). Furthermore, we observed that ovariectomy increases the vasoconstricting responses to the ET B agonist and that estrogen replacement therapy restores IRL-1620-induced responses, supporting our suggestion that the ovarian hormones modulate ET-1/ ET B receptor vascular responses/expression in DOCA-salt hypertension (50). Sexual dimorphism in vascular reactivity to ET-1 was also reported in SHR (51).…”
Section: Endothelinsupporting
confidence: 82%
“…Changes in ET Bmediated vascular responses were associated with increased ET-1 and ET B receptor gene expression in male, but not in female, animals (49). Furthermore, we observed that ovariectomy increases the vasoconstricting responses to the ET B agonist and that estrogen replacement therapy restores IRL-1620-induced responses, supporting our suggestion that the ovarian hormones modulate ET-1/ ET B receptor vascular responses/expression in DOCA-salt hypertension (50). Sexual dimorphism in vascular reactivity to ET-1 was also reported in SHR (51).…”
Section: Endothelinsupporting
confidence: 82%
“…Testosterone-induced production of nitric oxide (3), relaxation of various vascular beds (16,66), decrease of total cholesterol, low-density lipoprotein and triglycerides, and formation of endothelial progenitor cells (21) may account for the protective effects of the androgen in the cardiovascular system. However, reports of sudden cardiovascular death among male athletes abusing of anabolic steroids and the fact that in many experimental models of hypertension [spontaneously hypertensive rats (54), Dahl salt-sensitive rats (13), genetically hypertensive rats (1), and rats with deoxycorticosterone acetate-saltinduced hypertension (15)], males have higher levels of arterial pressure, which are abrogated by orchiectomy (9,54), indicate that testosterone is detrimental to the cardiovascular system. In addition, testosterone has been shown to directly affect many of the mechanisms that control cardiovascular function, such as the renin-angiotensin-aldosterone system, sympathetic neural activity, endothelial function, and VSMC tone (7,14,40).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] This steroid hormone contributes not only to the development of arterial hypertension but also to hypertensionassociated vascular and renal abnormalities. 6 In humans, it is still controversial whether testosterone contributes to or protects from cardiovascular disease.…”
mentioning
confidence: 99%